Professional attitudes and behaviors acquired during undergraduate education in the College of Dentistry, King Saud University - Dina Al-Sudani; Fatima Al-Abbas; Zainab Al-Bannawi; Anwaar Al-Ramadhan (Saudi Dental Journal)
Objectives: The purpose of the study was to investigate and evaluate the professional attitudes and behaviors acquired by students and recently graduated dentists during undergraduate education at King Saud University. Methods: This cross-sectional survey used a 27-item questionnaire covering four cumulative theoretical dimensions of professionalism. Questionnaires were distributed to fifth-year students, interns, and demonstrators in the College of Dentistry during the academic year 2010–2011, and 203 completed questionnaires were used in analyses. Descriptive statistics were used to summarize responses. Crosstab and chi-squared tests were used, with statistical significance set at P < 0.05. Results: The response rate was 79.3% (43.6% of males, 94% of females). Eighty-seven questionnaires were collected from fifth-year students, 92 from interns, and 24 from demonstrators. Many (59%) participants demonstrated high levels of professional attitudes and behaviors, whereas 40% did not comply with the elements of professionalism. Analyses revealed highly significant differences in certain responses with regard to gender, academic level, and grade point average. Conclusions: Although some participants did not possess all professional qualities, all participants possessed at least some elements of professionalism measured in this study. We thus recommend a strategic effort to develop targeted plans emphasizing professionalism at all levels of the dental school curriculum. High-profile role modeling, lectures, seminars, and academic ceremonies are ways of achieving professional development among dental students in parallel with their acquisition of basic scientific knowledge and clinical skills. This approach will formally and informally communicate that professionalism is a core value. Keywords: Professionalism, Attitudes, Behavior